Obesity induced transcriptional changes in skeletal muscle across different species. - Yujie Wang; Jiaman Zhang; Xintong Yang; Fuwen Wang; Long Jin; Jing Li; Xuewei Li; Mingzhou Li (PLoS ONE, 2025)
Pigs on high-fat diets maintaining metabolic homeostasis and are resistant to hepatic steatosis, differing from humans and mice. Obesity-induced metabolic dysregulation and inflammation in skeletal muscle are well-studied in humans and mice, but less is known about pig skeletal muscle responses. This study constructs the skeletal muscle transcriptome of obese pigs and integrates it with publicly available transcriptional profiles from obese humans and mice, and ATAC-seq data from lean individuals across species. We systematically characterized transcriptional changes in skeletal muscle under stress of obesity, focusing on the evolution of gene families, orthologous genes, and epigenetic regulation. Our results show that obesity activates lipid catabolism genes and inhibits immune response genes in pig skeletal muscle, contrasting with humans and mice. We identify expanding gene families in pigs, such as olfactory receptors, α-amylase, and ABC transporters, which are upregulated in obesity. While oxidative metabolism-related gene families are contracted in the human and mouse genomes and are downregulated with obesity. By comparing orthologous genes, we identify a set of divergently changing genes induced by obesity across species, which primarily participate in lipid metabolism, inflammation, and immune cell activation. High-divergence genes show conserved coding and promoter sequences, and exhibit greater chromatin accessibility in promoter regions, compare with low-divergence genes. These findings suggest that gene dosage and transcriptional plasticity contribute to species-specific expression divergent responses to obesity. Identifying rapidly evolving gene families, divergently expressed genes, and potential transcription factor binding sites may reveal new insights into obesity-related metabolic disorders and therapeutic targets.